Renal artery occlusion in autosomal dominant polycystic kidney disease. (August 2014) - Sánchez, María; Enríquez, Ricardo; Sirvent, Ana E.; Millan, Isabel; de la Iglesia, Pedro; Amorós, Francisco
Abstract Several vascular abnormalities have been reported in autosomal dominant polycystic kidney disease (ADPKD). Occlusion of the renal artery is uncommon in ADPKD and can be associated with hypertension. We report a 38-year-old woman with ADPKD and severe hypertension, abdominal magnetic resonance angiogram and arteriography revealed left renal artery total occlusion. A revascularization approach was not considered feasible and she was given conservative treatment. We review the literature and make some comments about renal artery occlusion in ADPKD. This association should be kept in mind in cases of ADPKD with severe or resistant hypertension.